Prototype Sistem Monitoring Level Air Sebagai Upaya Deteksi Banjir Secara Real Time Dengan Menggunakan Node Mcu Dan Website.docx - Renaldi Alamsyah; Fitri Yanti (Journal of Research and Publication Innovation, 2023)
Supervision of the water level in both canals and rivers is a job that is not too hard, but if there is negligence in monitoring the consequences are very detrimental because it involves the safety of the people around it. Not only that, the delivery of information about the water level is also very minimal. So that when the rainfall is high, residents who live around the canal/river don't have enough time to fix things that need to be secured. Uncontrolled water discharge due to extreme rainfall can make a channel overflow due to lack of information, this is due to the absence of a system that functions to provide real time and accurate water level information. One area of technology that is developing is microcontroller technology. The application of microcontroller technology is a Microcontroller-Based Water Level Monitoring Prototype. In designing this tool, using the ESP 6288 microcontroller as a data processor and an Ultrasonic sensor as a height meter. For early notification of a flood disaster, it is necessary to observe intensive and effective water level monitoring, so that the concerns of residents around the canal/river can be dismissed because of accurate information.